Optical packet switching in core networks between vision andreality. - El-Bawab, T.S.
The research on optical packet switching (OPS) has witnessed considerable progress in the 1990s. We examine the future potential of OPS in the core network by discussing this switching approach and the current status of a number of its enabling technologies. Many of these technologies are still in the stage of research and experimentation. We see that optical packet switching may be deployed in the long-term future subject to satisfaction of three main conditions/developments. First, additional technological developments have to take place to overcome remaining implementation challenges while making OPS cost-effective to deploy. Second, a rational migration scenario of the network toward gradual deployment of packet-based optical switching approaches should exist. Finally, carriers have to become more interested in packet-based optical switching solutions
Keywords: Internet protocol; Internet traffic; OPS-based nodes; WDM; Circuit-switched OXC-based network architectures; Core network; Optical cross-connects.; Optical packet switching research